Question Number 35152 by Victor31926 last updated on 16/May/18
Commented by Rasheed.Sindhi last updated on 16/May/18
$$\mathrm{x}+\mathrm{y}+\mathrm{z}=\mathrm{1}……………\mathrm{I} \\ $$$$\mathrm{x}^{\mathrm{2}} +\mathrm{y}^{\mathrm{2}} +\mathrm{z}^{\mathrm{2}} =\mathrm{35}……….\mathrm{II} \\ $$$$\mathrm{x}^{\mathrm{3}} +\mathrm{y}^{\mathrm{3}} +\mathrm{z}^{\mathrm{3}} =\mathrm{97}……….\mathrm{III} \\ $$$$\mathrm{II}\Rightarrow\left(\mathrm{x}+\mathrm{y}+\mathrm{z}\right)^{\mathrm{2}} −\mathrm{2xy}−\mathrm{2yz}−\mathrm{2zx}=\mathrm{35} \\ $$$$\:\:\:\Rightarrow\mathrm{1}−\mathrm{2xy}−\mathrm{2yz}−\mathrm{2zx}=\mathrm{35} \\ $$$$\:\:\:\Rightarrow\mathrm{xy}+\mathrm{yz}+\mathrm{zx}=−\mathrm{17} \\ $$$$\mathrm{III}\Rightarrow\mathrm{x}^{\mathrm{3}} +\mathrm{y}^{\mathrm{3}} +\mathrm{z}^{\mathrm{3}} −\mathrm{3xyz}=\mathrm{97}−\mathrm{3xyz} \\ $$$$\:\:\:\:\left(\mathrm{x}+\mathrm{y}+\mathrm{z}\right)\left(\mathrm{x}^{\mathrm{2}} +\mathrm{y}^{\mathrm{2}} +\mathrm{z}^{\mathrm{2}} −\mathrm{xy}−\mathrm{yz}−\mathrm{zx}\right) \\ $$$$\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:=\mathrm{97}−\mathrm{3xyz} \\ $$$$\:\:\:\left(\mathrm{1}\right)\left(\mathrm{35}−\left(−\mathrm{17}\right)\right)=\mathrm{97}−\mathrm{3xyz} \\ $$$$\:\:\:\:\:\:\:\:\:\:\mathrm{xyz}=\left(\mathrm{97}−\mathrm{52}\right)/\mathrm{3}=\mathrm{15}………\mathrm{IV} \\ $$$$\mathrm{I}:\:\:\:\:\mathrm{x}+\mathrm{y}+\mathrm{z}=\mathrm{1}\: \\ $$$$\mathrm{IV}:\:\:\:\:\:\:\mathrm{xyz}=\mathrm{15} \\ $$$$\mathrm{Assuming}\:\mathrm{x},\mathrm{y},\mathrm{z}\in\mathbb{Z} \\ $$$$\:\:\:\:\:\:\:\:\:\:\:\mathrm{xyz}=\mathrm{15} \\ $$$$\:\:\:\:\:\:\:\:\:\:\mathrm{1}.\mathrm{3}.\mathrm{5}=\mathrm{15}\:\mathrm{but}\:\mathrm{1}+\mathrm{3}+\mathrm{5}\neq\mathrm{1} \\ $$$$\mathrm{Some}\:\mathrm{numbers}\:\mathrm{must}\:\mathrm{be}\:−\mathrm{ve}\:\mathrm{and}\:\mathrm{in}\:\mathrm{order} \\ $$$$\mathrm{to}\:\mathrm{make}\:\mathrm{the}\:\mathrm{product}\:+\mathrm{ve}\:\mathrm{we}\:\mathrm{must}\:\mathrm{take} \\ $$$$\mathrm{any}\:\mathrm{two}\:\mathrm{of}\:\mathrm{x},\mathrm{y},\mathrm{z}\:\mathrm{negative}. \\ $$$$\mathrm{So}\:\mathrm{we}\:\mathrm{have} \\ $$$$\:\:\:\:\left(−\mathrm{1}\right)\left(−\mathrm{3}\right)\left(\mathrm{5}\right)=\mathrm{15} \\ $$$$\:\:\:\:\left(−\mathrm{1}\right)+\left(−\mathrm{3}\right)+\left(\mathrm{5}\right)=\mathrm{1} \\ $$$$\mathrm{Hence}\:\left\{\mathrm{x},\mathrm{y},\mathrm{z}\right\}=\left\{−\mathrm{1},−\mathrm{3},\mathrm{5}\right\} \\ $$
Commented by behi83417@gmail.com last updated on 16/May/18
$${xy}+{z}\left({x}+{y}\right)=−\mathrm{17}\Rightarrow\frac{\mathrm{15}}{{z}}+{z}\left(\mathrm{1}−{z}\right)=−\mathrm{17} \\ $$$$\Rightarrow{z}^{\mathrm{3}} −{z}^{\mathrm{2}} −\mathrm{17}{z}−\mathrm{15}=\mathrm{0} \\ $$$$\left({z}+\mathrm{1}\right)\left({z}^{\mathrm{2}} −\mathrm{2}{z}−\mathrm{15}\right)=\mathrm{0}\Rightarrow{z}=−\mathrm{1},−\mathrm{3},\mathrm{5} \\ $$$$\left({x},{y},{z}\right)=\left(−\mathrm{1},−\mathrm{3},\mathrm{5}\right),\left(−\mathrm{3},\mathrm{5},−\mathrm{1}\right),\left(\mathrm{5},−\mathrm{1},−\mathrm{3}\right). \\ $$